2012
DOI: 10.1088/0957-4484/23/19/194003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced absorption in silicon nanocone arrays for photovoltaics

Abstract: Silicon nanowire arrays have been shown to demonstrate light trapping properties and promising potential for next-generation photovoltaics. In this paper, we performed systematic and detailed simulation studies on the optical properties of silicon nanocone arrays as compared to nanowires arrays. Nanocone arrays were found to have significantly improved solar absorption and efficiencies over nanowire arrays. Detailed simulations revealed that nanocones have superior absorption due to reduced reflection from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 32 publications
0
93
0
Order By: Relevance
“…The absorption coefficient of CZTS is greater than 10 4 / cm and therefore only a thin layer (1-2 lm) can absorb most of the incident photons (Zhao and Qiao et al 2014;Mainz et al 2014;Fan 2014;Tanaka et al 2007;Chen et al 2009;Yu et al 2012). It is known that nanocone structure is an optimal shape for enhancing the light absorption (Wang and Leu 2012). In the study of Wang et al it has been reported that nanocone arrays significantly improve the solar absorption and efficiencies over nanowire arrays (Hsu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The absorption coefficient of CZTS is greater than 10 4 / cm and therefore only a thin layer (1-2 lm) can absorb most of the incident photons (Zhao and Qiao et al 2014;Mainz et al 2014;Fan 2014;Tanaka et al 2007;Chen et al 2009;Yu et al 2012). It is known that nanocone structure is an optimal shape for enhancing the light absorption (Wang and Leu 2012). In the study of Wang et al it has been reported that nanocone arrays significantly improve the solar absorption and efficiencies over nanowire arrays (Hsu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, periodic vertical cone arrays form a promising family of structures that are currently under examination for PV technology. Wang et al proved that the light absorption can be considerably enhanced by using nanocones [69,70]. In addition, Ko et al [71] demonstrated that an ultimate efficiency of 28.9% can be obtained by decreasing the cone bottom diameter to 20 nm.…”
Section: State Of the Art Of Semiconductor Nanowire Solar Cellsmentioning
confidence: 99%
“…In this table, the calculated values of ƞ, J sc , V oc , FF, and PCE of the cylindrical [66], conical [70], Si funnel [29], and proposed plasmonic funnel SiNWs are listed in detail. It may be noted from this table that the V oc and PCE of the plasmonic funnel shape are higher than that reported in Refs.…”
Section: Plasmonic Funnel Sinwsmentioning
confidence: 99%
“…However, weak absorption, especially in the long wavelength that near the vicinity of silicon bandgap edge, remains a challenge. To address this problem, textured active layer into nanostructure array have been extensively studied, such as nanowire [1][2][3], nanocone [4][5][6], nanohole and nanocone hole (NCH) [7,8] arrays. Among these, NCH arrays have been demonstrated with a promising capabilities of harvesting sunlight over a large wavelength [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The top-sided NCH structure is mainly used for increasing the antireflection of incident light, while the bottom-sided NCH structure plays an important role in light trapping to achieve broadband absorption enhancement. Due to mechanical robustness and cost-effective fabrication process as compared to nanocone array [4][5][6], the proposed model possesses industrial manufacturing value.…”
Section: Introductionmentioning
confidence: 99%